Species characterization of soft bottom habitats by depth and sediment particle size on the Catalan coast (NW Mediterranean): unexpected species composition of the assemblages - PINEDO, SUSANA; JORDANA, ESTHER; BALLESTEROS, ENRIC (Mediterranean Marine Science, 2022)
The aim of the study is to describe the macrofaunal composition of marine soft bottom habitats on the Catalan coast between a depth of 3 and 35 meters, considering all groups of macroinvertebrates. The study also aims to compare our data with previous studies focused on the NW Mediterranean and to define the variables that drive assemblage composition. Depending on the species composition and the structure of the assemblages, six different habitats, mainly defined by depth and sediment granulometry, are described. Shallow (<20 m) and deep (>20 m) habitats are easily distinguished and are subdivided in three habitats each: (1) very coarse and coarse sediments (coarse sediments); (2) medium, fine and very fine sands (fine sediments); and (3) muddy sediments. Fine sediments in both shallow and deep waters have emerged as the most common and extensive habitats along the coast up to a depth of 35 meters. Neither coarse nor muddy habitats are frequent. The characterization of shallow habitats produced some unexpected results with respect to previous studies: Spisula subtruncata and Lucinella divaricata were dominant, while neither Ditrupa arietina nor Owenia fusiformis, previously mentioned as dominant polychaetes in shallow fine sand habitats, were common. Polychaetes were, in general, the dominant group (both in species richness and abundance) in the six habitats, except in shallow fine sediments, which were dominated by mollusks. The study is a benchmark for future monitoring of soft bottom habitats on the Catalan coast to a depth of 35 meters.